Mechanism of Mesenchymal Stem Cells as a Multitarget Disease- Modifying Therapy for Parkinson's Disease - Unnisa, Aziz; Dua, Kamal; Kamal, Mohammad A. (Current Neuropharmacology, 2023)
Parkinson’s disease (PD) is one of the most prevalent neurodegenerative disorders, affecting the basal nuclei, causing impairment of motor and cognitive functions. Loss of dopaminergic (DAergic) neurons or their degeneration and the aggregation of Lewy bodies is the hallmark of this disease. The medications used to treat PD relieve the symptoms and maintain quality of life, but currently, there is no cure. There is a need for the development of therapies that can cease or perhaps reverse neurodegeneration effectively. With the rapid advancements in cell replacement therapy techniques, medical professionals are trying to find a cure by which restoration of dopamine neurotransmitters can occur. Researchers have started focusing on cell-based therapies using mesenchymal stem cells (MSCs) due to their abundance in the body, the ability of proliferation, and immunomodulation. Here we review the MSC-based treatment in Parkinson's disease and the various mechanisms it repairs DAergic neurons in parkinsonian patients.
Keywords: therapy